2005
DOI: 10.1080/02652030500412154
|View full text |Cite
|
Sign up to set email alerts
|

Conditions of formation of ochratoxin A in drying, transport and in different commodities

Abstract: The major species of fungi responsible for ochratoxin production (OTA) in a range of commodities are Penicillium verrucosum, Aspergillus ochraceus and Aspergillus section Nigri, especially A. carbonarius. P. verrucosum is particularly important in northern Europe where damp cooler conditions occur and where drying regimes need to be efficient and effective for preventing post-harvest contamination with OTA. A. ochraceus can infect cereals including barley, maize, coffee, cocoa and edible nuts. A. carbonarius h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 33 publications
(33 reference statements)
3
62
0
Order By: Relevance
“…Wheat is the natural habitat of this species, and the results described here show that apparently the natural environment actively supports OTA biosynthesis by this fungus, comparable with the activation of the biosynthesis by the very supportive YES medium. Aspergilli are not commonly associated with production of important amounts of OTA in wheat at lower temperature (described in Magan and Aldred 2005). However, A. ochraceus BFE635 and A. niger BFE632 produced the highest amounts of OTA (>50 μg OTA/g agar) at 25°C in wheat-based medium.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Wheat is the natural habitat of this species, and the results described here show that apparently the natural environment actively supports OTA biosynthesis by this fungus, comparable with the activation of the biosynthesis by the very supportive YES medium. Aspergilli are not commonly associated with production of important amounts of OTA in wheat at lower temperature (described in Magan and Aldred 2005). However, A. ochraceus BFE635 and A. niger BFE632 produced the highest amounts of OTA (>50 μg OTA/g agar) at 25°C in wheat-based medium.…”
Section: Discussionmentioning
confidence: 94%
“…Environmental conditions, such as temperature and moisture expressed as water activity (a w ), pH and nutrient content of the matrix, incubation time, and light, are decisive factors for fungal OTA production (Abellana et al 2001;Astoreca et al 2007;Esteban et al 2004;Magan and Aldred 2005;Richter et al 2001;Schmidt-Heydt et al 2010, 2011. Penicillium species are known as OTAproducers in regions with temperate and cold climates.…”
Section: Introductionmentioning
confidence: 99%
“…Grape washing, cooking and pressing can also promote the OTA content drop [53,287]. During vine fruits production, efficient drying and turning over are required because in these stages, moisture and sugar content stimulates Aspergillus section Nigri development and OTA synthesis [288].…”
Section: Microbiological Methodsmentioning
confidence: 99%
“…The maximum level of OTA allowed in dried vine fruits in Europe is 10 µg/kg (12). Moreover, Aspergillus niger aggregate and Aspergillus carbonarius have been blamed as the OTA producers in grape and grape-derivatives (13)(14)(15). Astoreca et al (16) reported that, throughout the grape drying process, the biodiversity index showed a decreasing trend because the water activity (Aw) of grape was decreasing and the sugar level was increasing.…”
Section: Introductionmentioning
confidence: 97%